50.9k views
5 votes
Let V(x)=−x2+2x−4 and W(x)=−x3+2x2+x+5. Find V(x)−W(x).

User Scherling
by
6.6k points

2 Answers

5 votes

Answer:

x³ - 3x² + x - 9

Explanation:

V(x) - W(x) =

- x² + 2x - 4 - (- x³ + 2x² + x + 5) ← distribute parenthesis by - 1

= - x² + 2x - 4 + x³ - 2x² - x - 5 ← collect like terms

= x³ - 3x² + x - 9

User Willbill
by
6.2k points
7 votes

Answer:

Explanation:

v(x) - W(x) = x² + 2x - 4 - [x³ + 2x² + x + 5]

= x² + 2x - 4 - x³ - 2x² -x - 5

= x² - 2x² - x³ + 2x - x -4 - 5

= -x² - x³ + x - 9

User Noproblem
by
5.9k points